Negative bureaucratic behavior in the regulation of taxicab businesses the case of the Board of Transportation - Bautista, Victoria A. (1979)
Procedures in the normal processing of papers relative to the taxicab business are examined to determine the type of corruption that takes place in the Board of Transportation as an example of a regulatory agency of the government. Factors that contribute to the commission of corruption are identified: (1) the cultural value of particularism; (2) the absence of rational and objective procedures in assessing papers, equipment or clients; (3) the culture of corruption prevailing in the agency; and (4) the incapability of the leadership to lead by example. While the positive impact of corruption in terms of expeditious processing of papers and lesser costs to agency and clientele is recognized, its overall dysfunctional effect in terms of unfair and unjust treatment of clients outweigh whatever benefits corruption may provide.
Keywords: Transportation policy; Government agencies -- Corrupt practices; Corruption -- Government policy; Board of Transportation (BOT)